A Comparison of the Effectiveness of Antibiotic Therapy and Surgical Treatment in Patients with Acute Appendicitis - Rdzanek, Bartłomiej; Żelazo, Jakub; Wacławek, Katarzyna; Janawa, Kamil; Bacik, Małgorzata; Głodowska, Klaudia; Ciesielka, Anna; Rechcińska, Aleksandra; Kiereta, Kacper; Cichowska, Zuzanna; Chmielowiec, Laura (Quality in Sport, 2025)
Acute appendicitis is one of the most common causes of abdominal pain requiring emergency surgical intervention. While appendectomy has long been the standard treatment, recent evidence has explored the use of antibiotics as a non-operative alternative, particularly for uncomplicated cases. In this study, we want to compare the effectiveness, safety, and long-term outcomes of antibiotic therapy versus surgical appendectomy in the management of acute appendicitis. A comprehensive review of recent randomized controlled trials (RCTs), including the APPAC and CODA trials, as well as meta-analyses, was conducted to evaluate treatment success rates, recurrence, complications, costs, and patient preferences. Results: Antibiotic therapy successfully avoided surgery in most of the cases (approximately 73%) of patients within one year,. However, recurrence rates reached up to 39%. Surgical treatment was associated with lower recurrence (<5%) but higher direct costs and longer recovery. Antibiotic therapy resulted in shorter hospital stays and reduced overall treatment costs. Patient-centered decision-making was found to play a crucial role in selecting the appropriate therapy. Conclusions: Antibiotic therapy represents a safe and cost-effective alternative to appendectomy for selected patients with uncomplicated acute appendicitis. However, shared decision-making and proper patient selection are essential to optimize outcomes and minimize risks. Further research is needed to refine the criteria for non-operative management and ensure long-term safety. The aim of the study: This study aims to compare the effectiveness, safety, and long-term outcomes of antibiotic therapy versus surgical appendectomy in the management of acute appendicitis.